Effect of Coexisting TiO2 Powder on Ionic Conduction of Highly Concentrated LiTFSA Aqueous Electrolyte (20.5 mol kg−1) - Jingchao XU; Hideshi MAKI; Hiro MINAMIMOTO; Minoru MIZUHATA (Electrochemistry)
An electrical conductivity and its activation energy are measured for solid-liquid coexistence systems consisting of TiO2 powder/highly concentrated LiTFSA aqueous electrolyte (20.5 mol kg−1). The conductivity increases exponentially with an increase of the liquid content up to ca. 40 vol%, and the activation energy of the conductivity increases with a decrease of the liquid content below 35 vol%. Various spectroscopic measurement, such as Raman, near-infrared (NIR), and NMR spectra indicated that the presence of TiO2 disrupts the nanoscale water channel structure in the water-enriched regions of the bulk solution in the TiO2 powder/20.5 mol kg−1 LiTFSA solid-liquid coexistence system with a liquid phase volume fraction below 40 vol%, resulting in an unusual decrease in the electrical conductivity. The strong influence of the solid phase on the electrical conduction of the highly concentrated LiTFSA electrolyte was found to be significant only in the region below 50 vol% in the liquid content, while in the region of the liquid content above 50 vol%, there were no differences due to electrolyte concentration and ion species, indicating the influence of the solid phase on electrical conduction.